Applying risk management to the management of innovative enterprises - A. O. Verenikina (Путеводитель предпринимателя, 2022)
The activities of innovative enterprises entail various risk situations. Organisations should be able to identify perceived risks and minimise them. Innovative enterprises, whose activities are known to be the most risky, should try their best to establish a risk management process.Empirical and theoretical research methods were used in writing the paper: analysis, synthesis of the studied theoretical data, method of generalization, graphical method. The subject of the research in this article is risk management as a constituent link in the management and development of innovative enterprises. The article considers the importance of applying risk management. The author has identified important stages of risk management in the management of innovative enterprises, developed an appropriate information model.